Konsep-Konsep Matematika oleh Ilmuwan Muslim - Muhammad Hidayat; Hasrian Rudi Setiawan; Arwin Juli Rakhmadi (Proceeding International Seminar of Islamic Studies, 2019)
Mathematic has been regarded as a subject that is often presented with a series of technical procedures without meaning in various syllabi and textbooks. Mathematics also functions to solve problems of daily life and worship of Muslims such as the calculation of Zakat, Inheritance, Qibla Direction, Prayer Times, Eclipses, Hijriyah Calendar etc.Some mathematical concepts described by Islamic Scientist Al-Khawarizmi (232 H / 846 AD) The greatest work of Al-Khawarizmi is his work in the field of al-jabar written in the span of 813-833 AD, titled (Kitab fi al-Jabr wa al- Muqabala) Many scientists give the name al-Khawarizmi as "Father of Algebra." Although many of them state that al-Khawarizmi is inspired by other scientists such as Diophantus, Euclid, Heron, Brahmagupta, and Aryabhata, in this paper we will discuss mathematical concepts. Muslim scientists and al-Khawarizmi's State of the Art will be discussed which distinguishes it from other Scientist works.